2013
DOI: 10.1016/j.ccr.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Function of BRCA1 in the DNA Damage Response Is Mediated by ADP-Ribosylation

Abstract: SUMMARY Carriers of BRCA1 germline mutations are predisposed to breast and ovarian cancers. Accumulated evidence shows that BRCA1 is quickly recruited to DNA lesions and plays an important role in the DNA damage response. However, the mechanism by which BRCA1 is recruited to DNA damage sites remains elusive. BRCA1 forms a Ring-domain heterodimer with BARD1, a major partner of BRCA1 that contains tandem BRCT motifs. Here, we identify the BRCTs of BARD1 as a poly(ADP-ribose) (PAR)-binding module. The binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
278
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 278 publications
(289 citation statements)
references
References 71 publications
8
278
1
2
Order By: Relevance
“…S9A). This is consistent with other findings that PAR also mediates the fast recruitment of other DNA damage repair factors to DNA lesions (15,16). To examine the nature of the relatively fast DNA damage repair mediated by hSSB1, we used siRNA to deplete XRCC1, a key factor for ssDNA damage repair (33-37).…”
Section: Ints3supporting
confidence: 59%
See 1 more Smart Citation
“…S9A). This is consistent with other findings that PAR also mediates the fast recruitment of other DNA damage repair factors to DNA lesions (15,16). To examine the nature of the relatively fast DNA damage repair mediated by hSSB1, we used siRNA to deplete XRCC1, a key factor for ssDNA damage repair (33-37).…”
Section: Ints3supporting
confidence: 59%
“…Recent evidence suggests that DNA damage-induced PAR may serve as a docking signal to recruit DDR factors to DNA lesions (7)(8)(9)(10)(11)(12)(13)(14). For example, our recent study showed that the BRCT domains of BARD1 and NBS1 recognize PAR, which facilitates the rapid recruitment of the BRCA1/BARD1 complex and NBS1 to the site of DNA damage (15,16). These results indicate that other DDR factors may also be recruited to DNA damage sites by PAR.…”
mentioning
confidence: 84%
“…However, based on the peptide screening, not all of the FHA and BRCT domains have high affinity to phospho-proteins (Durocher et al 2000;Rodriguez et al 2003). In particularly, our recent study suggests that the BARD1 BRCT domain recognizes ADP-ribose (Baer 2013;Li and Yu 2013). Thus, we asked whether these domains have other binding partners besides phospho-proteins.…”
mentioning
confidence: 99%
“…Chromatin relaxation allows access to DNA repair factors, some of which are recruited through binding PAR. PARP1 mediates the initial accumulation of MRE11–RAD50–NBS1 (MRN) complex at DNA lesions and promotes rapid recruitment of BRCA1, BRCA2 and EXO1 involved in homologous recombination [2629]. PAR also promotes recruitment of XRCC1 as a scaffold protein in base excision repair [17,30,31] and XPA as a scaffold protein in nucleotide excision repair [32].…”
Section: Introductionmentioning
confidence: 99%
“…By cleaving PAR, PARG promotes timely protein dissociation from DNA damage sites, as shown in the case of BRCA1, XRCC1, CHD2 and TRIM33 [25,26,43,44]. …”
Section: Introductionmentioning
confidence: 99%